Implementation of Work Life Balance and its Impact on Employee Retention in Systematic Literature Review - Thamara, Shely Dinar; Anshori, M Isa (Formosa Journal of Applied Sciences, 2024)
This study aims to analyze the factors that influence employee retention using the Systematic Literature Review (SLR) method. Based on the results of the analysis of various studies, it was found that a good working environment, career development opportunities, and job security are the main factors that influence employees' decisions to stay in the company. Although work-life balance is often considered important, its influence on employee retention varies, depending on the context. Other factors, such as company incentives, rewards, and flexible policies, also play a role in increasing employee loyalty. This study provides insight for companies to design more effective HRM policies, so as to increase employee retention, reduce turnover, and support organizational sustainability.